Laser gun system :measurement and comparison - Abdullah, Ali (Universiti Malaysia Sarawak (UNIMAS), 2002)
This thesis is to design the measurement system of actual speed of vehicle with considering all of the potential error. This thesis also doing comparison between Laser Gun models with considering a few aspect for specifications each Laser Gun model.